The use of sewage sludge ash (SSA) as partial replacement of cement in concrete - Tan, Kim Guan (2015)
The production of sewage sludge from waste water treatment plant is increasing all over the world. Disposal of sewage sludge is becoming a serious environmental problem. Another alarming issue is attributed to the high usage of concrete in the construction industry where concrete is one of its main material. This will lead to increased cement production and emission of carbon dioxide because the cement industry one of the major contributor of carbon dioxide emission. Hence, the research for replacement of cement by sewage sludge ash is essential to reduce both the emissions of carbon dioxide and the disposal problem of sewage sludge ash. An attempt has been made to investigate the use of sewage sludge ash as partial cement replacement in concrete. The sewage sludge is incinerated at the temperature of 600°C and a duration of 3 hours. The incinerated sewage sludge ash is sieved through size of 150 µm. Four different percentages of 5%, 10%, 15% and 20% of sewage sludge ash (SSA) is used to replace the cement in the concrete. XRD and XRF tests were carried out to determine the similarity component present in the SSA. Water absorption test and slump test has also been carried out to check the capacity of water absorption, durability and workability of the SSA concrete. The compressive strength of SSA concrete is also determined through rebound hammer and compression test. Results show that SSA has the potential to replace cement as the major chemical component of SSA is similar to that of cement.5% of SSA concrete shows a lower absorption value than the control sample which shows that 5% SSA would have a better durability. However, an increase in the percentage of SSA decreases the workability and compressive strength and yet, the 5% SSA concrete possesses compressive strength higher than 25 N/mm 2 which can be applied in structural applications. The findings suggested that the suitability of sewage sludge ash concrete in different cement replacement ratio is applicable for different usage. The application of sewage sludge ash in concrete will directly reduce the quantity of the cement used which also decreases the emissions of carbon dioxide and solving the disposal problem of sewage sludge.